PENGGUNAAN THINK TALK WRITE (TTW) DENGAN MENYERTAKAN HAND OUT UNTUK MEMBANTU PEMAHAMAN SISWA PADA MATERI PERSAMAAN GARIS LURUS DI MTSN KEPANJEN - Fahrudin, Fadrik Adi (MEJ (Mathematics Education Journal), 2017)
Students of State Islamic Junior High School (MTsN) Kepanjen find themselves difficult in understanding a chapter of straight line equation. The learning method used is considered to be text book oriented and being teacher centered learning. This research aims to increase students participatory and be more student centered learning. It used a new model of learning called Think Talk Write (TTW) along with passing out the hand out to students. This too attempts to have students understanding regarding a chapter of straight line equation.Type used was classroom action research and held on a eigth year students of MTsN Kepanjeng. Object of this research were students of class VIII-C and were divided into nine group, each one consists of four students. They were grouped based on their degree of ability ranging from high, moderate and low. Data collected was analysed using data reduction, presenting and drawing conclusion toward students test result, observation, interview and field notes. Teacher distributed hand out to students and they have been asked individually to read and think through the contents. The objective was to gain preliminary  nowledge. Afterwards, they worked in group to discuse the idea and concept as well as doing the assigments. Teacher as a facilitator brainstormed the concept and guide students to present it in front of class. By the end of the class, students and teacher have got together to make a conclusion of all. The result showed TTW along with the hand-out have able to improve students understanding over straight line equation. The final test showed the students grade of accomplishment has reached by 88,89%.